Ambulatory blood pressure in schoolchildren. Issue 6 (1st June 1999) - O'Sullivan, J J; Derrick, G; Griggs, P; Foxall, R; Aitkin, M; Wren, C
Abstract : OBJECTIVE: To define the range and variability of ambulatory blood pressure in normal schoolchildren. DESIGN: Prospective study. METHODS: Resting blood pressure of 1121 schoolchildren from Newcastle upon Tyne was recorded. An ambulatory blood pressure device, which uses both auscultatory (Korotkoff) and oscillometric methods of blood pressure measurement, was then put in place for 24 hours. RESULTS: The day was divided into three time periods: school, home, and night time. Normal centiles for blood pressure for each of these time periods were obtained and many daytime readings were outside reported normal resting levels. The normal variation of blood pressure was quantified by comparing each of these time periods with the resting readings. Resting systolic blood pressure did not predict 24 hour mean systolic blood pressure. CONCLUSIONS: The availability of normal ambulatory blood pressure data on the level and variation of blood pressure in children may facilitate the early identification of hypertension in this age group.